2017
DOI: 10.1088/1361-6528/aa6aef
|View full text |Cite
|
Sign up to set email alerts
|

Annealing of Au, Ag and Au–Ag alloy nanoparticle arrays on GaAs (100) and (111)B

Abstract: Part of developing new strategies for fabrications of nanowire structures involves in many cases the aid of metal nanoparticles (NPs). It is highly beneficial if one can define both diameter and position of the initial NPs and make well-defined nanowire arrays. This sets additional requirement on the NPs with respect to being able to withstand a pre-growth annealing process (i.e. de-oxidation of the III-V semiconductor surface) in an epitaxy system.Recently, it has been demonstrated that Ag may be an alternati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
16
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 48 publications
(81 reference statements)
1
16
0
Order By: Relevance
“…Analysis of the anneal-ing temperature and cooling rate on the crystallographic orientation of AuNPs has shown that annealing at lower temperature yields more faceted, larger particles with a wider size distribution. 58 The surface orientation of the substrates appears to affect the mobility and crystal structure of AuNPs, 59 however AuNPs formed on amorphous SiO 2 -glass substrates also show faceting, preferring the {111} orientation. 58 The formation of nanoparticles (NPs) by annealing occurs as a result of the processes of coalescence, Ostwald ripening, or as a combination of the two.…”
mentioning
confidence: 99%
“…Analysis of the anneal-ing temperature and cooling rate on the crystallographic orientation of AuNPs has shown that annealing at lower temperature yields more faceted, larger particles with a wider size distribution. 58 The surface orientation of the substrates appears to affect the mobility and crystal structure of AuNPs, 59 however AuNPs formed on amorphous SiO 2 -glass substrates also show faceting, preferring the {111} orientation. 58 The formation of nanoparticles (NPs) by annealing occurs as a result of the processes of coalescence, Ostwald ripening, or as a combination of the two.…”
mentioning
confidence: 99%
“…We find that a relatively high V/III ratio combined with an oxide masked substrate 39,40 increases the yield of these inclined NWs. However, the initial growth depends on the details of the catalyst interaction with the substrate 41,42 , which also 9 influence the preferential NW morphology and crystal structure. We also find that the NW crystal structure changes from ZB to pure WZ during the initial growth stage, under the given growth conditions 13,43,44 .…”
mentioning
confidence: 99%
“…We find that a relatively high V/III ratio combined with an oxide masked substrate , increases the yield of these inclined NWs. However, the initial growth depends on the details of the catalyst interaction with the substrate, , which also influence the preferential NW morphology and crystal structure. We also find that the NW crystal structure changes from ZB to pure WZ during the initial growth stage, under the given growth conditions. ,, Growth of two NWs along the opposite ⟨111⟩B directions, stemming from seed particles positioned along the [0–11] direction, then results in the formation of the vertical X-shaped WZ/ZB/WZ NCs (Figure a, left panel).…”
mentioning
confidence: 99%
“…Recently, the spontaneous motion of Au droplets on III–V surfaces has been studied due to the role of this metal particle in vapor–liquid–solid mechanism, usually employed in III–V nanowire growth. In particular, the ability to control droplet crawling opens up the possibility to create novel structures and to facilitate nanowire integration in device fabrication, through a process totally determined by an in situ mechanism, which can reach similar size limits as electron beam lithography. The fabrication of oxide free surfaces by Au droplet crawling has already been observed; however, the direct impact of Au droplet motion in nanowire growth to create novel morphologies has not been determined yet.…”
mentioning
confidence: 99%
“…Spontaneous temperature-activated motion of liquid metal droplets on III–V semiconductor surfaces has already been reported, especially for Ga droplets. In this case, droplet dynamics have been shown to be intrinsically associated with differences in surface roughness on solid surfaces, such as the local step density; , in general, the motion can be interpreted as a result of the surface free energy gradient under nonequilibrium conditions, caused by changes in surface roughness . Recently, the crawling of liquid droplets has been observed and studied in more detail for Au nanoparticles, where vacuum conditions and the introduction of water vapor during the heating step have been demonstrated to affect droplet stability. Despite chemical and surface energy differences for Ga and Au droplets on III–V surfaces, we can expect some common features.…”
mentioning
confidence: 99%